Private Placements and Minority Interests: The Philippine Case - Cayanan, Arthur S. (Philippine Management Review; Vol 24 (2017), 2017)
Some of the biggest listed Philippine companies had issued more shares through private placements. In most cases, the private placement offer prices are at a significant discount over the prevailing market price of the stock at the time of the offer. This study attempted to quantify wealth loss effects of private placements on minority stockholders and to assess the adequacy of regulatory safeguards on this practice. The roles of the Philippine Stock Exchange and the independent directors are also examined in protecting the interest of small investors with respect to this issue.